Changing within the same class: efficacy of brodalumab in plaque psoriasis after treatment with an IL-17A blocker – a retrospective multicenter study. (17th November 2021) - Kromer, C.; Wilsmann-Theis, D.; Gerdes, S.; Krebs, S.; Pinter, A.; Philipp, S.; Mössner, R.
Abstract: Introduction: Biologic switching is common in psoriasis patients with non-response to or adverse events under therapy with a biologic. However, evidence on efficacy of switching between newly approved biologics of similar mode of action is scarce. The objective was to assess the efficacy of treating psoriasis patients with an IL-17-receptor A antagonist after failure of any IL-17A antagonist and to identify predictors of treatment response. Methods: A retrospective multicenter chart review on psoriasis patients who received brodalumab after failure of ixekizumab or secukinumab therapy was conducted in five German University Medical centers. Results: Overall, 23 patients were identified. PASI75 response to brodalumab was reached by 47.8% (11/23) of all patients at week 12 and at week 24. 3 patients experienced mild adverse events which did not lead to drug discontinuation. Conclusions: Brodalumab appears to be an efficacious and safe treatment option in psoriasis patients with prior exposure to IL-17A antagonists.